Collaboration Between Industrial, Collaborative, Humanoid Robots and Humans. - Vjatsheslav Kekshin; Sergei Ponomar; Martinš Sarkans; Vladimir Kuts; Sergei Pavlov (Journal of Machine Engineering)
One of the key aspects of Industrial Revolution 5.0 is the reintegration of humans into the industrial environment. This process enhances the interaction between various robots and humans in industry. It addresses challenges such as the large number of able-bodied workers, which limits the replacement of human resources with humanoid robots in production processes. The need for humanoid robots is particularly relevant in environments that are unsafe and pose significant health risks to humans. People with disabilities will be able to work effectively in environments where humanoid and collaborative robots are used. The scientific article explores the concept of Industry 5.0, focusing on the methodology for implementing and integrating technologies within the framework of smart manufacturing.